Geografiske hol i ei nasjonal ordbok – om geografisk representasjon av kjeldene i Norsk Ordbok - Karlsen, Knut E. (Nordiske Studier i Leksikografi, 2006)
Geographical holes in a national dictionary – about geographical representation of the sources in Norsk Ordbok. Norsk Ordbok covers both the written language ’nynorsk’ and the spoken language in Norway. As a national dictionary, there is a demand for geographical representation when it comes to the spoken language. Nevertheless this survey shows that the spoken language in the northern part of Northern Norway and in most cities, is very poorly documented. The main reason for this seems to be a heritage from an earlier neogrammatical influenced linguistic tradition which was characterised by studies with Old Norse as one comparative component. Little attention was paid to dialects which were a product of language contact, which is the case for both the dialects in the northern part of Northern Norway and in the cities until late in the 1970's. Norsk Ordbok was organised as a project i 2002 and there is now some effort put in balancing the source material with a view to geographical representation.